2008
DOI: 10.1007/s11671-008-9225-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Temperature on Bamboo-shaped Carbon–Nitrogen (C–N) Nanotubes Synthesized Using Ferrocene Acetonitrile Precursor

Abstract: This investigation deals with the effect of growth temperature on the microstructure, nitrogen content, and crystallinity of C–N nanotubes. The X-ray photoelectron spectroscopic (XPS) study reveals that the atomic percentage of nitrogen content in nanotubes decreases with an increase in growth temperature. Transmission electron microscopic investigations indicate that the bamboo compartment distance increases with an increase in growth temperature. The diameter of the nanotubes also increases with increasing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
52
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 53 publications
11
52
0
4
Order By: Relevance
“…The CNT structure is characterized by a highly regular arrangement of carbon atoms leading to a high crystallinity. The Raman spectrum showed that the I G /I D decreased from 5.70 to 1.71 when the MWCNTs were doped with N; this result is in accordance with that previously reported for N-doped CNTs [18][19][20][31][32][33]. The decrease in I G /I D indicates a decrease in the crystallinity of carbonaceous structures, which, in this case, was due to the defects created by the N atoms.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The CNT structure is characterized by a highly regular arrangement of carbon atoms leading to a high crystallinity. The Raman spectrum showed that the I G /I D decreased from 5.70 to 1.71 when the MWCNTs were doped with N; this result is in accordance with that previously reported for N-doped CNTs [18][19][20][31][32][33]. The decrease in I G /I D indicates a decrease in the crystallinity of carbonaceous structures, which, in this case, was due to the defects created by the N atoms.…”
supporting
confidence: 90%
“…The short f-MWCNTs could be beneficial for gas transportation through the inner cavities of the tubes because of CNTs with an increased number of open ends and a more uniform dispersion due to their decreased length. Nitrogen doping has been proven to be an effective method to tailor the electrical properties as well as the chemical reactivity of CNTs [15][16][17][18][19][20]. However, the use of N-doped CNTs for obtaining shortened nanotubes has not been reported thus far.…”
mentioning
confidence: 99%
“…Raman spectroscopy has been widely used to examine crystallinity and reveal the defects in carbon structures by identifying even slight changes in orientation of CAC bonds [35]. Fig.…”
Section: Surface Analysis: Raman and Ftir Spectroscopymentioning
confidence: 99%
“…π * -резонанс молекулярного азоту продемонстрував чітку поляризаційну залежність, що свідчить про переважну орієнтацію молекуль N 2 вздовж вісі ВНР. У випадку синтези бамбукоподібних N-ВНР з використанням фероцен-ацетонітрилу встановлено, що атомова частка азоту у ВНР зменшується зі збільшенням температури [41]. Середня довжина жмутів ВНР складала 430 мкм.…”
Section: а бunclassified